Implementasi GARASI (Gerakan Literasi Islami) melalui Buku Kisah Nabi untuk Meningkatkan Budaya Membaca Siswa TPQ - Sofiyah, Salsabila; Nabila Rifdah Arisanti; Alya Zahra A’thifah; Maulida Fifah Amalia; Balqis Addurrunnafisa; Siti Miyatul Fauziah; Hilyatul Mu’minah; Jessica Ambiya; Subandriyo (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Abstract. The literacy culture in Taman Pendidikan Al-Qur’an (TPQ) still faces challenges since children’s reading activities are generally limited to learning Baca Tulis Al-Qur’an (BTQ), while reading storybooks has not yet become a habit. This condition underlies the implementation of a community service program with the theme of Islamic literacy, aiming to foster reading interest while strengthening children’s character values. The objective of this activity is to develop a literacy culture through the implementation of the GARASI (Gerakan Literasi Islami) program based on prophetic stories, integrated with 15-minute reading habits, reading journal writing, and reward mechanisms. The method applied was Participatory Action Research (PAR), involving 49 students of TPQ Baitul Ilmi Ceria Palumbonsari, Karawang Timur, along with teachers and TPQ administrators. The results show improvements in soft skills, including motivation, reading initiative, and the ability to reflect on moral values from readings, while hard skills were reflected in the development of basic writing abilities through reading journals. This program also fostered more active and creative literacy practices, although challenges such as time constraints, limited book collections, and insufficient parental involvement remain. Therefore, the implementation of GARASI proves to be a strategic step in strengthening children’s Islamic literacy culture in a sustainable manner.